Gafchromic EBT films for ion dosimetry - Martišíková, Mária; Jäkel, Oliver (Radiation measurements, 2010)
For dose delivery to patients, scanning ion beams are going to be increasingly used in the upcoming ion beam therapy facilities. Especially carbon ion beams are able to produce steep dose gradients. However, the currently used method for patient dose verification, employing ionization chamber arrays, provides a spatial resolution of 1 cm only.